Impact of Ultraviolet Radiation on the Pigment Content and Essential Oil Accumulation in Sweet Basil (Ocimum basilicum L.) - Natalya A. Semenova; Alexandr A. Smirnov; Alina S. Ivanitskikh; Andrey Yu. Izmailov; Alexey S. Dorokhov; Yuri A. Proshkin; Denis V. Yanykin; Ruslan R. Sarimov; Sergey V. Gudkov; Narek O. Chilingaryan (Applied Sciences, 2022)
In this study, we investigated the effects of additional ultraviolet radiation (UV) on the main growth fluorescent lamp light on pigment content and essential oil accumulation in sweet basil (Ocimum basilicum L.). Three different UV light sources from light-emitting diodes and discharge lamps, which emit UV in the UV-A (315–400 nm), UV-B (280–315 nm) and UV-C (100–280 nm) ranges, were tested for basil plant growing. The plants, growing under additional UV-A and UV-B from mercury lamps, on the 60th growing day were higher than control plants by 90% and 53%, respectively. The fresh leaf mass of the UV-A irradiated basil plants was 2.4-fold higher than the control plant mass. The dry mass/fresh mass ratio of the UV-A and UV-B irradiated plants was higher by 45% and 35% in comparison to the control plants. Leaf area was increased by 40% and 20%, respectively. UV-C affected the anthocyanin content most strongly, they increased by 50%, whereas only by 27% and 0% under UV-A and UV-B. Any UV addition did not affect the essential oil total contents but altered the essential oil compositions. UV-A and UV-B increased the linalool proportion from 10% to 20%, and to 25%, respectively, in contrast to UV-C, which reduced it to 3%. UV-C induced the eugenol methyl ether accumulation (17%) and inhibited plant growth. Moreover, UV increased the proportion of α-guaiene, β-cubebene and α-bulnesene and decreased the proportion of sabinene and fenchone. Thus, we concluded that UV (except UV-C) used jointly with main light with PPFD 120 ± 10 μmol photons·m−2·s−1 for sweet basil cultivation may be justified to stimulate basil growth and optimize the essential oil accumulation.